Air and Moisture Transport Properties of Low‐Oil DDGS. Issue 6 (13th September 2017) - Bhadra, Rumela; Ambrose, R. P. Kingsly; Casada, Mark E.; Simsek, Senay; Siliveru, Kaliramesh
Abstract : Distillers dried grains with solubles (DDGS) are widely used as feed for cattle, dairy, and swine because of their protein, fiber, amino acids, fat, and other vital nutrients. Corn ethanol plants in the United States recently have started extracting oil from DDGS to gain additional profit, thus producing low‐oil DDGS. So far, there has been no comprehensive study reported with bulk handling and flowability properties of low‐oil DDGS. We measured the air resistance, moisture diffusivity, and air permeability properties for low‐oil DDGS at different temperature and relative humidity conditions, along with some important physical and chemical properties. Physical property comparisons between regular and low‐oil DDGS showed differences in key properties such as particle size, color, density, porosity, and angle of repose. The modified Henderson model predicted the equilibrium moisture content (EMC)–equilibrium relative humidity (ERH) relationship of low‐oil DDGS with a low standard error of regression value (0.008); it showed no pattern in the residuals and was judged the most appropriate model tested for EMC‐ERH predictions. Results of EMC‐ERH nonlinear modeling were used to define conditions for moisture diffusivity. Moisture diffusivities of low‐oil DDGS at varying drying temperatures ranged from 0.74 × 10 −11 to 1.77 ×10 −11 m 2 /s. The properties are important for understanding and modeling heat and moisture transport through and flow properties of low‐oil DDGS.